Determinan opini audit Going Concern: Financial Distress sebagai variabel moderasi menggunakan Logistics Regression Analysis - Yosafat Chrizar Ratu Nagari; Dwi Suhartini (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to examine the effect of KAP reputation, auditor switching, leverage and financial distress in moderating the effect of KAP reputation, auditor switching, leverage on the acceptance of going concern audit opinions. The sample in this study is 103 companies listed on the Indonesia Stock Exchange in the 2017-2020 period which are classified based on Consumer Non-Cyclicals shares because they have the largest population compared to other sectors and these companies are more complex because they have to produce and sell finished goods. The sampling technique in this study uses purposive sampling method, namely the data required must have certain criteria, so that the obtained sample size is 15 companies (60 data). While the data collection technique in this study uses a documented approach, where the data in this study comes from the official website of the Indonesia Stock Exchange (IDX) at https://www.idx.co.id/ and the websites of each sample company. The analysis technique uses Logistic regression analysis using the Statistical Package for Social Science (SPSS) 24 Version. The results of the analysis prove that there is no significant effect of KAP reputation and audit switching on going concern audit opinions; there is a significant effect of leverage on going concern audit opinion; there is no significant effect of financial distress strengthening the influence of KAP reputation and audit switching on going-concern audit opinion; and there is a significant effect of financial distress strengthening the effect of leverage on going-concern audit opinion. These results prove that financial distress functions as a moderating variable for leverage on going concern audit opinion